Primary pulmonary meningioma — a rare lung tumor - Galust A. Baksiyan; Alexander A. Zavialov; Sergey V. Lishchuk (Клиническая практика)
BACKGROUND: Primary pulmonary meningioma is a rare and clinically non-diagnosable tumor. Foreign literature describes not more than 70 cases of this disease. The tumor represents a single solid node, not having any specific features, which does not allow for setting the clinical diagnosis before the pathologic examination. The disease has various occurrence rates both among women and men. The diagnosis is to be set based on the morphological examination of the surgical material with small dimensions of the tumor (or biopsy samples for cases of large tumor). CLINICAL CASE DESCRIPTION: The patient А. (54 years of age) with a history of combined treatment 9 years ago due to being diagnosed with рТ2аN1М0, stage IIIB cervical cancer. According to the results from the computed tomography of the chest cavity organs, in segments S8/9 of the lower lobe of the right lung, the findings included a subpleural solid mass lesion with the size of 14×11 mm. According to data from further examinations (computed tomography of the chest cavity organs, of the abdominal cavity and of the minor pelvis; magnetic resonance tomography of the brain; esophagogastroduodenoscopy; colonoscopy), no other abnormalities were detected. Surgical treatment was arranged at the extent of thoracoscopic atypical resection of the lower lobe of the right lung. Anatomic pathology examination report on the resected tumor indicates the presence of “Pulmonary meningioma”. CONCLUSION: This clinical case represents the first documented experience of surgical resection of primary pulmonary meningioma in Russia.